SYNTHESIS OF SORBENTS USED IN THE SEPARATION OF HALOGENS - Murtazaev, F.I.; Raximov, G.B. (Sanoatda raqamli texnologiyalar, 2023)
The article studied the synthesis of sorbents for the extraction of three halogens, and used sorption methods to concentrate metal vagalogen ions. Ion-exchange and complex-forming polymers and polymer materials were obtained, and ion-exchange materials were obtained on the basis of polyacrylonitrile and polyvinyl chloride obtained at "Navoyazot" OJSC.